What Motivates People to Start a Graduate Entry Nursing Programme: An Interpretive Multi-Centred Case Study - Rachel Macdiarmid DHSc, RN; Patricia McClunie-Trust RN; Kay Shannon MN, RN; Rhona Winnnington PhD, RN; Andrea E. Donaldson PhD, RN; Rebecca J. Jarden PhD, RN; Rachel Lamdin-Hunter PhD, RN; Eamon Merrick PhD, RN; Rosemary Turner RN; Virginia Jones RN (SAGE Publishing, 2021)
Introduction While graduate entry nursing programmes are well established in the United Kingdom and the United States of America (USA), they are relatively new to New Zealand and Australia. These programmes have been developed to meet the demands of the health workforce and provide graduates an alternative pathway to becoming a RN. Nursing is viewed as an attractive career option for this growing market of graduate entry students. Objective This study explored the motivations underpinning students choosing a graduate entry MNSc degree over a traditional undergraduate nursing programme. Methods A qualitative, longitudinal single case study design, informed by Yin was used. The first phase of the study is reported here. All students commencing a MNSc degree at the beginning of 2020 across four education providers (3 in New Zealand & 1 in Australia) were eligible to take part in the study. Ten students agreed to take part and undertake an interview. Braun and Clarke's approach to thematic analysis was used to analyse the interview data. Results Three key themes of motivation were identified from the data: the attraction of nursing; the clarity nursing offers in terms of career progression; and the design of the intensive programme. Conclusions The motivations to choose a MNSc degree were deeply considered, multifaceted, and influenced by nursing role models. Students wanting to engage with a graduate entry MNSc programme did so through a reflective process of assessing their current career status and future career values. Participants in this study believed nursing would provide a secure and sustainable career path, potentially creating new horizons or possibilities beyond their previous work and life experiences. Having insight into what motivates individuals to enrol in such programmes may assist both education providers and the health sector with RN graduate recruitment and graduate entry programme enrolment.